2020
DOI: 10.1021/jacs.0c00909
|View full text |Cite
|
Sign up to set email alerts
|

Multielectron, Cation and Anion Redox in Lithium-Rich Iron Sulfide Cathodes

Abstract: Na 2 S was prepared from stoichiometric Na (Acros Organics, rod, 99.8%, mechanically cleaned prior to use) and S (see main text) in separate alumina crucibles (Almath) in an evacuated silica ampoule. The reactants were heated at 1°C min −1 to 300°C for 48 h and cooled ambiently to room temperature. The ground product was a fine powder of a slightly tan-color. The product was determined to be phase pure by XRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
214
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(224 citation statements)
references
References 74 publications
9
214
1
Order By: Relevance
“…23 , 25 , 26 Recent work has also shown that anion redox involving sulfur can be important in controlling reaction pathways. For example, sulfides such as VS 4 27 , 28 and Li 2 FeS 2 29 undergo reversible ion intercalation/deintercalation reactions involving coupled S 2– /S 2 2– beside transition-metal redox couples.…”
Section: Introductionmentioning
confidence: 99%
“…23 , 25 , 26 Recent work has also shown that anion redox involving sulfur can be important in controlling reaction pathways. For example, sulfides such as VS 4 27 , 28 and Li 2 FeS 2 29 undergo reversible ion intercalation/deintercalation reactions involving coupled S 2– /S 2 2– beside transition-metal redox couples.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Recently,Saha et al presented fundamental research on the bottlenecks of Sr edox, [17] in which an ew material Li 1.33À2y/3 Ti 0.67Ày/3 Fe y S 2 (y = 0.3) was capable of ar eversible capacity as high as 245 mAh g À1 .T he high capacity resulted from the existence of 3d 6 electrons in the Fe 2+/3+ redox couple that activated the anionic Sr edox. During the final review stage of this manuscript, See et al revealed the electrochemistry of aL i-rich layered iron sulfide Li 2 FeS 2 , [18] whereas Zhao-Karger reported on multivalent cation storage in VS 4 , [19] further emphasizing the rising importance of this class of materials.…”
Section: Introductionmentioning
confidence: 99%
“…23,25,26 Recent work has also show that anion redox involving sulfur can be important in controlling reaction pathways. For example, sulphides such as VS4 27,28 and FeS2 29 undergo reversible ion intercalation-deintercalation reactions involving coupled S 2− /S 2 2− beside transition-metal redox couples.…”
Section: Introductionmentioning
confidence: 99%